The central importance of ecological spatial connectivity to effective coastal marine protected areas and to meeting the challenges of climate change in the marine environment. (September 2017) - Carr, Mark H.; Robinson, Sarah P.; Wahle, Charles; Davis, Gary; Kroll, Stephen; Murray, Samantha; Schumacker, Ervin Joe; Williams, Margaret
Abstract: The several forms of ecological spatial connectivity – population, genetic, community, ecosystem – are among the most important ecological processes in determining the distribution, persistence and productivity of coastal marine populations and ecosystems. Ecological marine protected areas (MPAs) focus on restoring or maintaining marine populations, communities, or ecosystems. All ecological MPAs – no matter their specific focus or objectives – depend for their success on incorporating ecological spatial connectivity into their design, use (i.e. application), and management. Though important, a synthesis of the implications of ecological spatial connectivity for the design, use, and management of MPAs, especially in the face of a changing global climate, does not exist. We synthesize this information and distill it into practical principles for design, use, and management of MPAs and networks of MPAs. High population connectivity among distant coastal ecosystems underscores the critical value of MPA networks for MPAs and the populations and ecosystems between them. High ecosystem connectivity among coastal ecosystems underscores the importance of protecting multiple connected ecosystems within an MPA, maximizing ecosystem connectivity across MPAs, and managing ecosystems outside MPAs so as to minimize influxes of detrimental organisms and materials into MPAs. Connectivity‐informed MPAs and MPA networks – designed and managed to foster the ecological spatial connectivity processes important to local populations, species, communities, and ecosystems – can best address ecological changes induced by climate change. Also, the protections afforded by MPAs from direct, local human impacts may ameliorate climate change impacts in coastal ecosystems inside MPAs and, indirectly, in ecosystems outside MPAs.